ANALYSIS OF SCIENCES STUDENT PROBLEM SOLVING SKILSS AT JUNIOR HIGH SCHOOL STUDENTS IPA LESSONS - M W Hutagaol (UNIVERSITAS NEGERI MEDAN, 2021)
The purpose of this study was to analyze the students' science problem solving abilities class IX ondynamic electricity at SMP Negeri 3 Medan. The research method used is descriptive qualitative. Inthe study, using the subject of 20 students. Technique the sampling used is random sampling. Theresults showed that. The science problem solving ability of class IX students at SMP Negeri 3Medan is still classified as low. This can be seen from the acquisition of research results as follows:at the stage identify the problem that is (33.25%), the percentage of the total stage of describing theproblem is (35 %), the total percentage of the planning stage of the solution is (65 %), the totalpercentage of the stage Implement problem solving solutions, namely (50%) and indicators Conductevaluations of (64.50%). Based on the results of the average score of the five stages, the averagescore the lowest student's science problem solving ability was at the stage of identifying problem.